The social media MBA in practice : an essential collection of inspirational case studies to influence your social media strategy - Holloman, Christer (Wiley, 2013)
"The inside information that marketers and social media practitioners have been dying to get hands on. It seems like every day another self-appointed social media "guru" appears on the scene, offering to sell you his or her "surefire" cure for what ails you. Don't you think it's time you heard from the real experts--i.e., folks like you who are responsible for delivering their companies' social media strategies? Based on extensive interviews with marketing, media and networking professionals at many of today's most admired brands and companies, this book provides you with detailed examples of the social media strategies in place at, among others, Virgin Atlantic, Barclays, Skype, Dell, John Lewis, Ranstad, Honda, HP, E.con, and Chevrolet. The most comprehensive set of "blueprints" available in one book for delivering social media strategies more successfully Includes in-depth case studies packed with hand-on-advice that you can put to work in your company immediately Covers all-important strategic social media activities--from improving relationships with customers to generating more sales, product testing to team building The Companion Website features a gold mine of additional material, updates, war stories and much more"--